Studies on structural, optical, thermal and photoconductivity of a new organic nonlinear optical crystal: 4-methylpyridinium 4-nitrobenzoate. (7th June 2018) - Shalini, D.; Kalainathan, S.; Mohan Kumar, R.; Revathi Ambika, V.; Jayalakshmi, D.
Abstract: Good-quality new single crystals of 4-methylpyridinium 4-nitrobenzoate were grown by slow evaporation solution growth technique at room temperature using methanol as solvent. The structure of the crystal confirmed by single-crystal X-ray diffraction and it revealed that the grown crystal crystallised into triclinic system with the space group P . The presence of various functional groups was identified by FT-IR analysis. Transmission range of the crystal was determined by UV–vis–NIR spectra and cut-off wavelength was found to be 395 nm. Photoconductivity studies of 4M4N divulged its negative photoconducting nature. The crystal is thermally stable up to 105.74 °C as determined by thermo gravimetric–differential thermal analysis. The third-order non-linear optical parameters (non-linear refractive index, non-linear absorption coefficient and real and imaginary parts of the third-order non-linear optical susceptibility) measured by Z-scan technique proved that 4M4N crystal possesses two-photon absorptions. The positive refractive index value indicates the self focusing nature of the crystal.